The Budgetary and Performance Influences of Product Standardization and Manufacturing Process Automation - Brownell, Peter; Merchant, Kenneth A. (Journal of Accounting Research, 1990)
Peter Brownell, Kenneth A. Merchant, The Budgetary and Performance Influences of Product Standardization and Manufacturing Process Automation, Journal of Accounting Research, Vol. 28, No. 2 (Autumn, 1990), pp. 388-397